Comparing classical performance measures for a multi-period, two-echelon supply chain network design problem with sizing decisions - Isabel Correia; Teresa Melo; Francisco Saldanha-da-Gama (Hochschule für Technik und Wirtschaft des Saarlandes, Fakultät für Wirtschaftswissenschaften, 2012)
This paper addresses a new problem to design a two-echelon supply chain network over a multi-period horizon. Strategic decisions are subject to a given budget and concern the location of new facilities in the upper and intermediate echelons of the network as well as the installation of storage areas to handle different product families. A finite set of capacity levels for each product family is available at each potential location. Further decisions concern the quantities of products to be shipped through the network. Two mixed-integer linear programming models are proposed that differ in the type of performance measure that is adopted to design the supply chain. Under a cost minimization objective, the network configuration with the least total cost is to be determined. In contrast, under a profit maximization goal the aim is to design the network so as to maximize the difference between total revenue and total cost. In this case, it may not always be attractive to completely satisfy demand requirements. To investigate the implications that the choice of these performance measures have on network design, an extensive computational study is conducted using randomly generated instances that are solved with a general-purpose solver.
Keywords: 650; supply chain network design; facility location; capacity acquisition; profit maximization; cost minimization; Lieferkette; Logistik; Lagerinvestition; Lagerzyklus; Performance-Messung